Some properties of m-th root Finsler metrics - A. Tayebi; A. Nankali; E. Peyghan (Հայաստանի ԳԱԱ)
We prove that every m-th root metric with isotropic mean Berwald curvature reduces to a weakly Berwald metric.
Keywords: Mathematics; Science